1999
DOI: 10.1046/j.1365-2036.1999.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E in gastric mucosal injury induced by ischaemia‐reperfusion in nitric oxide‐depleted rats

Abstract: These results indicate that the inhibition of lipid peroxidation and interference with neutrophil infiltration by vitamin E may be responsible for its cytoprotective effect in ischaemia-reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…More and more evidence suggests that the majority of injuries occur during reperfusion [3][4][5], and this may be attributable to reactive oxygen metabolites initially generated at the level of the vasculature [6]. Sources of reactive oxygen metabolites in reperfusing tissues include the xanthine oxidase system, which produces superoxides and hydrogen peroxides during reperfusion [7,8], and activated neutrophils, which infiltrate into the tissues and bind to the microvascular endothelium [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…More and more evidence suggests that the majority of injuries occur during reperfusion [3][4][5], and this may be attributable to reactive oxygen metabolites initially generated at the level of the vasculature [6]. Sources of reactive oxygen metabolites in reperfusing tissues include the xanthine oxidase system, which produces superoxides and hydrogen peroxides during reperfusion [7,8], and activated neutrophils, which infiltrate into the tissues and bind to the microvascular endothelium [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Naito et al 22) have shown that vitamin E protects against ischemia-reperfusioninduced gastric mucosal injury under nitric oxide depletion in rats by inhibiting not only lipid peroxidation but also neutrophil infiltration in the gastric mucosal tissue. We have reported that neutrophil infiltration into gastric mucosal tissues contributes to not only the formation but also the progression of C48/80-induced acute gastric mucosal lesions in rats.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Yoshikawa et al 21) reported that both a decrease in gastric mucosal vitamin E level and an increase in gastric mucosal lipid peroxidation occurred during the development of ischemia-reperfusion-induced gastric mucosal injury in rats and that the severity of ischemia-reperfusion-induced gastric mucosal injury was enhanced in vitamin E-deficient rats. Naito et al 22) have shown in nitric oxide-depleted rats that vitamin E plays an important role in protecting against ischemia-reperfusion-induced gastric mucosal injury, and have suggested that this gastroprotective effect of vitamin E is due to not only its antioxidant action but also its inhibitory action on neutrophil infiltration into the gastric mucosa. Al-Dhohyan and Al-Tuwaijri 23) reported that a single oral pre-admin- The effect of oral vitamin E administration on acute gastric mucosal lesion progression was examined in rats treated once with compound 48/80 (C48/80) (0.75 mg/kg, i.p.)…”
mentioning
confidence: 99%
“…Hypovolemia-related injury has not been studied adequately in animals. Currently, there are also no related human data available on this phase of tissue damage (9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the type of irritant that damages the gastric mucosa, production of these oxygen radicals plays a role in the tissue damage. It is well established that damaged tissue contains decreased levels of antioxidant enzymes and increased levels of lipid peroxidation products (1,(9)(10)(11)(12)(13)(14).…”
Section: Discussionmentioning
confidence: 99%